The Power of Writers in by-Phrase Agents: Textual Analysis in Research Methodology - Wongkittiporn, Abhinan (Asia Social Issues, 2025)
This study examined the power of writers in by-phrase agents used in applied linguistics research methodology. Previous studies focused on agentless passive voice in medical texts, academic texts, and business news. The results showed that people contextually interpreted the omitted agents of passive voice widely known agents, such as doctors, researchers, and businesspeople. Although the writers know the agents are contextually known and therefore use passive voice, it is intriguing to explore why they spell out the by-phrase agents in applied linguistics methodology. To investigate this fact, the study's method was purposive sampling. The data were SCOPUS Q1 databases from System, English for Specific Purposes and Studies in Second Language Acquisition, and reputable international publications. There were 45 applied linguistics research methodologies. The researchers collected all passive voice constructions with by-phrase agents in the methodology section and found a total of 52 tokens. The data analysis followed the PDI theory (power, distance, and imposition) (Brown & Levinson, 1987), the sociolinguistic framework of power and distance. The results of this study showed that the researchers discovered the power of artful passive voice through morphological and syntactic analysis. The researchers found the morphological feature in the plurality marker -s in 50 percent of the cases. The syntactic features of combined NP (noun phrase) and collective NP were found at 28.85 percent and 19.23 percent, respectively. The discussion in this study reveals that morphological inflections and syntactic noun phrases reflect the sociolinguistics of democratic power in English-speaking contexts. Even though the quality of a writer’s academic writing is influenced by various factors, the results of passive constructions and by-phase agents in this study allow us to visualize the formal tone of academic writing in English.